Efficacy of Ganoderma lucidum on plasma lipids and lipoproteins in rats fed with high cholesterol diet - Tong, Chow Chin; Choong, Yew Keong; Mohamed, Suhaila; Mohamed Mustapha, Noordin; Umar, Nor Aini (Emerald Group Publishing, 2008)
Purpose – The purpose of this paper is to report on the anti-cholesterol activities of Ganoderma lucidum on Sprague–Dawley white rats.